Design of a public health emergency equipment modularized system for bioterrorism events in major public places based on scenario analysis, literature review, cluster analysis, and Delphi consultation - Sun, Xiaowen; Zhang, Yongzhong; Zhao, Chao; Li, Tiantian; Bai, Song (Frontiers in Public Health, 2025)
ObjectiveTo improve the standardization of health emergency equipment at the scene of bioterrorism events in major public places and to establish a health emergency equipment modularized system for such events.MethodsBased on domestic laws and regulations, domestic and international literature on health emergencies from 2004 to 2023, and survey data on the equipment configuration of domestic health emergency equipment enterprises and relevant emergency response teams, this study first used scenario analysis to explore the functional requirements of health emergency equipment from three aspects: the environment in which bioterrorism events occur, the survival and task requirements of personnel at the scene, and the methods of emergency response. Second, with reference to national standards for the allocation of health emergency equipment, a preliminary plan for the equipment system was determined through literature analysis and market research. Then, a preliminary plan of the modularized system of health emergency equipment is formed through the cluster analysis method. Finally, the Delphi method was used to revise and improve the plan.ResultsThe positive coefficient of expert consultation in both rounds was 100%, and the mean coefficient of expert authority was 0.855. The coordination coefficients of the expert opinions were 0.226 and 0.258, respectively (both P < 0.001), indicating a good degree of coordination among the expert opinions. The final modularized system of health emergency equipment for bioterrorism events in major public places was established. This modularized system consisted of 5 first-level modules, 15 second-level modules, and 32 third-level modules, and is equipped 162 types of equipment.ConclusionThe constructed modularized system of health emergency equipment for bioterrorism events has a certain degree of pertinence and reliability and can serve as a reference for the construction of health emergency team equipment modularized systems and the use of health emergency equipment at the scene of bioterrorism events.